Digital Exploration in Indonesian Language Learning for Character Enhancement - Ali, Muttaqin Kholis; Ali, Al Muhtadi Billah (Jurnal Hata Poda, 2024)
Indonesian language learning in the digital era offers significant potential for enhancing students' character. This research explores digital exploration in the context of Indonesian language learning with a focus on improving student character. Qualitative research methods are used with a Systematic Literature Review (SLR) approach based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). Findings from this research highlight the importance of digital literacy, the use of conventional and digital media, and integrated language learning management with a 21st-century approach. The research indicates that the integration of digital technology in Indonesian language learning can enhance creativity, self-directed learning, and students' adaptability skills. However, challenges such as critical thinking inability, declining writing skills, and the effectiveness of online learning are also encountered. Recommendations for future research include further studies on the effectiveness of specific digital media, the development of innovative learning models, and the analysis of trends and innovations in the use of digital technology. Suggestions for educational practitioners include digital literacy training, the development of integrated curricula, and collaboration with technology industries to strengthen the implementation of digital technology in Indonesian language learning.